Aluminum electron energy loss spectra. A comparison between Monte Carlo and experimental data - Dapor, Maurizio (Frontiers in Materials, 2022)
One of the most interesting applications of the Monte Carlo method consists in the simulation of the energy loss spectrum of backscattered electrons when a solid target is bombarded with an electron beam of given kinetic energy. Knowing the elastic and inelastic scattering cross-sections of the electrons in their interaction with the atoms of the target, it is possible to calculate the probabilities of angular diffusion and the loss of kinetic energy for each collision between the electrons of the incident beam and the atoms of the target. In this way, it is possible to model the history of each electron following its trajectory and calculating its energy losses, its final energy, and the exit point from the target surface whether and where it exists. By averaging over a large number of trajectories, it is possible to obtain a spectrum representing the energy distribution of the backscattered electrons from any given solid target. This paper compares experimental and Monte Carlo data concerning reflection electron energy loss spectra. In particular, the paper is aimed at understanding the interplay between surface and bulk features for incident electrons in Al.